eHealth Literacy: From Theory to Clinical Application for Digital Health Improvement. Results from the ACCESS Training Experience - Roberta Bevilacqua (MDPI AG, 2021)
Skills, knowledge, and awareness of digital and technological tools are essential to improve the state of well-being and health of older adults and also to mitigate the condition of social isolation in the aging process. For this reason, it is necessary to implement a social learning of electronic/digital tools for health of older people to support the achievement of eHealth and digital competences. The paper reports the results of an Italian innovative eHealth training for the European project ACCESS. The training has been based on blended didactical and interactive educational techniques, aimed at collecting as many points of view as possible from older adults. A total of 58 older adults were recruited to attend a four-week training program, which included five modules. The results showed a statistical significant difference between the eHealth Literacy Scale (eHEALS) mean value before and after the course. A significant negative correlation was found between eHEALS and positive/total Survey of Technology Use (SOTU), suggesting an inverse relationship between positive/total SOTU and eHEALS. There is a strong positive and statistically significant relationship between satisfaction with the training and eHEALS. The results indicate that the intervention increased the digital competences of participants connected to health.